2007
DOI: 10.1128/iai.00652-07
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Serine Accumulation and Catabolism in the Colonization of the Murine Urinary Tract by Escherichia coli CFT073

Abstract: In this study we show that deletion of the genes encoding L-serine deaminases SdaA and SdaB resulted in a mutant that accumulates higher intracellular levels of L-serine than CFT073. CFT073 sdaA sdaB has a mild competitive colonization defect whereas a CFT073 dsdA sdaA sdaB triple mutant shows a greater loss in competitive colonization ability. Thus, the inability to generate serine-specific catabolic products does not result in hypercolonization and the ability to catabolize serine represents a positive physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
93
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 32 publications
4
93
1
Order By: Relevance
“…We have previously shown that D-serine is able to act as an intracellular signal, enhancing urinary tract colonization, but it also can serve as a key nutrient in the absence of L-serine catabolic potential (4). As shown in this work and in that of other laboratories, the catabolism of serine leads to the generation of acetyl phosphate (40,53), among other compounds, which aids signal transduction via several two-component regulatory systems (25,46,51,53).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…We have previously shown that D-serine is able to act as an intracellular signal, enhancing urinary tract colonization, but it also can serve as a key nutrient in the absence of L-serine catabolic potential (4). As shown in this work and in that of other laboratories, the catabolism of serine leads to the generation of acetyl phosphate (40,53), among other compounds, which aids signal transduction via several two-component regulatory systems (25,46,51,53).…”
Section: Discussionsupporting
confidence: 59%
“…The dashed line indicates a competitive index of 1.0. (4). When these observations are paired with our previous observations of the importance of the periplasmic stress response in colonization of the mouse model (42,43), the alterations in colonization associated with the dissimilatory acetate metabolism mutants seem likely due to an inability to accumulate acetyl phosphate, an inappropriate acetyl-CoA level, or an altered stress response.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…It has recently been suggested that bacterial metabolic capability enhances fitness and contributes to pathogenesis, which could provide an alternative explanation for the success of prevalent UPEC clones (16), and previous reports have shown that certain metabolic enzymes may also enhance virulence (22). For example, the ability of UPEC to catabolize the amino acid D-serine during UTI supports bacterial growth and acts as a signaling mechanism to trigger virulence gene expression (2,24).…”
mentioning
confidence: 99%